2011
DOI: 10.1038/modpathol.2011.40
|View full text |Cite
|
Sign up to set email alerts
|

Role and predictive strength of transglutaminase type 2 expression in premalignant lesions of the cervix

Abstract: The demonstration that type 2 transglutaminase (TG2) can incorporate polyamine into the E7 oncoprotein of human papillomavirus (HPV) type 18 has led to the hypothesis that TG2 can have a role in the host cellular response to HPV infection. The aim of this study was to investigate whether HPV-related pathology, in infected human cervical epithelium, was associated with modulation of TG2 expression. Normal controls and HPVinfected cervical biopsies were analyzed for the expression of TG2, and the findings were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Moreover, this enzyme is currently referred as a phenomenon not restricted to high-risk genotypes [3]. Present results corroborate previously published data [3,7], emphasizing that HSIL patients demonstrated a significant statistical association with low TG2 expression (p <0.05).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Moreover, this enzyme is currently referred as a phenomenon not restricted to high-risk genotypes [3]. Present results corroborate previously published data [3,7], emphasizing that HSIL patients demonstrated a significant statistical association with low TG2 expression (p <0.05).…”
Section: Discussionsupporting
confidence: 82%
“…Characterization of TG2 expression in normal cervix is seen in only two studies which investigated TG2 levels in samples such as these, even though this is relevant information. Both studies found negative expression in normal tissues, indicating that TG2 expression is solely related to non-malignant changes or LSIL [3,7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations